A multi-resolution approach to on-line signature intra-class variability modelling - Liew, Lee Hung (Faculty of Computer Science and Information Technology, 2005)
The current function approach of using a single resolution representation for on-line handwritten signature verification is unable to identify the inner variation of the features, which are caused by intra-class and interclass variability contained in the collected short signal. Such an approach might cause the acceptance of forged signatures that have similar patterns as the original and the rejection of genuine signatures that have high intra-class variability.